2008
DOI: 10.3892/mmr_00000030
|View full text |Cite
|
Sign up to set email alerts
|

Cyclooxygenase-2 expression in invasive transitional cell carcinoma of the urinary bladder

Abstract: Abstract. Cyclooxygenase-2 (COX-2) activity is reported to increase apoptosis, inhibit angiogenesis and reduce metastasis. We analyzed COX-2 expression in patients with invasive bladder cancer to evaluate the feasibility of selective COX-2 inhibitor treatment targeting COX-2. Forty patients with pathologically diagnosed invasive transitional cell carcinoma of the urinary bladder (pT2-pT4) were evaluated. Immunohistochemical staining was used to evaluate COX-2 expression, and cases with staining of ≥10% of tumo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
5
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 15 publications
(16 reference statements)
3
5
0
1
Order By: Relevance
“…This finding is consistent with some previous studies (Komhoff et al, 2000;Wulfing et al, 2004;Yamada et al, 2008;Naruse et al, 2010) and incompatible with the others (Matsuzawa et al, 2002;Shariat et al, 2003b;Wadhwa et al, 2005;Gurocak et al, 2006;Margulis et al, 2007;Jang and Lee, 2009). We also investigated whether there was any difference between muscle invasive tumors (≥P T2) and non -muscle invasive ones (Ta-T1) in the expression of COX-2, but we did not find any significant difference.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…This finding is consistent with some previous studies (Komhoff et al, 2000;Wulfing et al, 2004;Yamada et al, 2008;Naruse et al, 2010) and incompatible with the others (Matsuzawa et al, 2002;Shariat et al, 2003b;Wadhwa et al, 2005;Gurocak et al, 2006;Margulis et al, 2007;Jang and Lee, 2009). We also investigated whether there was any difference between muscle invasive tumors (≥P T2) and non -muscle invasive ones (Ta-T1) in the expression of COX-2, but we did not find any significant difference.…”
Section: Discussionsupporting
confidence: 78%
“…These contradictory results could be related to different causes such as limited number of cases or just selecting invasive bladder TCCs with grade 2 and 3 (Yamada et al, 2008;Naruse et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Similar previous findings were reported in previous studies [11, 32, 40]. But there are some other studies which failed to prove such association [29, 36]. Also, we reported that high COX-2 immunostaining is statistically associated with tumors with positive lymphovascular invasion similar to that of a previous report [36].…”
Section: Discussionsupporting
confidence: 92%
“…There are several studies reporting the same association [28, 32, 36]. On the other hand, other studies failed to show association between COX-2 expression and grade in UCB [20, 22, 24, 29, 37, 38].…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation